Pengaruh Board Game terhadap Pemahaman Konsep IPAS pada Siswa Kelas V Sekolah Dasar - Nur Afna Juanda; Atep Sujana; Enjang Yusup Ali (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The problem in this research is that students have not been able to explain the human respiratory process studied with their own understanding, students feel learning is not fun because of the lack of good supporting media. So, the aim of this research is to obtain an overview of the influence of using the Board Game